Distraction in a case of otopalatodigital syndrome type II - P. BATRA, F. S. RYAN, H. WITHEROW & M. L. CALVERT (Paediatric Dentistry, 2006)
Otopalatodigital syndrome type II is a rare X-linked recessive disorder with generalized skeletal dysplasia and hearing anomalies. Its features include conductive hearing loss, unusual facies, cleft palate, micrognathia, and overlapping flexed fingers and toes. It is a more lethal variant of otopalatodigital syndrome type I.